Tolerance and Persistence of Pseudomonas aeruginosa in Biofilms Exposed to Antibiotics: Molecular Mechanisms, Antibiotic Strategies and Therapeutic Perspectives - Soares, Anaïs; Alexandre, Kévin; Etienne, Manuel (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa biofilm-related infections are difficult to treat with antibiotics. Along the different layers of the biofilm, the P. aeruginosa population is heterogeneous, exhibiting an extreme ability to adapt his metabolic activity to the local microenvironment. At the deepest layers of the biofilm is a subset of dormant cells, called persister cells. Though antimicrobial failure might be multifactorial, it is now demonstrated that these persister cells, genetically identical to a fully susceptible strain, but phenotypically divergent, are highly tolerant to antibiotics, and contribute to antimicrobial failure. By eradicating susceptible, metabolically active cells, antibiotics bring out pre-existing persister cells. The biofilm mode of growth creates microenvironment conditions that activate stringent response mechanisms, SOS response and toxin-antitoxin systems that render the bacterial population highly tolerant to antibiotics. Using diverse, not standardized, models of biofilm infection, a large panel of antibiotic regimen has been evaluated. They demonstrated that biofilm growth had an unequal impact of antibiotic activity, colistin and meropenem being the less impacted antibiotics. Different combination and sequential antimicrobial therapies were also evaluated, and could be partially efficient, but none succeeded in eradicating persister cells, so that non-antibiotic alternative strategies are currently under development. This article reviews the molecular mechanisms involved in antibiotic tolerance and persistence in P. aeruginosa biofilm infections. A review of the antimicrobial regimen evaluated for the treatment of P. aeruginosa biofilm infection is also presented. While tremendous progress has been made in the understanding of biofilm-related infections, alternative non-antibiotic strategies are now urgently needed.